The Idea for a Multi – Speed Europe and the Process of EU Enlargement - Zafiroski, Jovan (BISI, Nice, 2020)
Seventy years after the start of the process of its creation, the world’s biggest and richest economic space, the European Union, is facing many challenges. The recent COVID 19 pandemic has provoked an economic “tsunami” and put in jeopardy the European unity. Amid these circumstances the debate for the future of Europe is more than important. The Rome Declaration from 2017 offers a possibility for different forms of integration for the Members of the EU i.e. multi-speed Europe. This will have a major impact as on the current structure of the EU as well as on the enlargement process. As the EU is heading towards uncharted territory the candidate and potential candidate countries should continue to work on reforms. The paper explains the roots of the idea for a multi-speed Europe and analyses the possible consequences for the Western Balkan countries in the integration process for EU membership.